The Growing Importance of the Financial Sector in the Founding Countries of the European Union - Tomasz Florczak (Finanse i Prawo Finansowe, 2020)
The economies of the 21st century countries operate on the principle of connected vessels. A significant element of changes in economies is the growth of the financial sector. The process of financial sector growth is often referred as financialization. The significant impact of this sector on economic development was shown during the financial crisis of 2008. Financialization is more visible in highly developed countries. Undoubtedly the founding countries of the European Union belong to highly developed countries. It is possible that the financialization is higher in bigger countries like France, Germany, Italy or United Kingdom, which can also have bigger financial sectors. From the other side there is also country, which economy is based on banks. The aim of the article is to indicate the growth of the financial sector in the founding countries of the European Union. To determine the growth of the financial sector, the author used the indicators appearing in the literature of subject. There are indicators relating to functioning of the economy and banking sector. The second method helps to determine in which country financialization is higher. To made the research there was used zero unitarization method. The results of the study allows to determine in which of the subjects the financial sector is at a higher level of development. It is possible, that during researched period there were changes in financializiation of researched countries.